Homeward Bound? Global Mobility and the Role of the State of Nationality During the Pandemic - Frédéric Mégret (AJIL Unbound, 2020)
The international law of mobility has by and large been focused on the question of immigration. Its emphasis has therefore been on what I will call, for convenience's sake, the host state. It is there that some of the most intense dilemmas around the question of mobility have arisen in a context of populism, xenophobia, and racism. The state of nationality is not invisible in that context, but this has not typically been the primary variable in trying to understand and assess the normative challenges of global mobility. The COVID-19 pandemic, however, has refocused attention on distinct patterns of mobility, particularly return mobility, of nationals to their country of origin as well as limitations on leaving that country in the first place. The state of nationality has increasingly been asked to mediate demands for security and public health that are extra-territorial and that implicate its nationals in sometimes far-flung locations. I argue that the pandemic is a further opportunity to shift attention onto the state of nationality as a locus of key decisions concerning transnational mobility and thus to rebalance our sense of what goes into the global “mobility equation.”